2000
DOI: 10.1176/ajp.157.1.148-a
|View full text |Cite
|
Sign up to set email alerts
|

Quetiapine and False-Positive Urine Drug Testing for Tricyclic Antidepressants

Abstract: provides important insight into the real cost of the treatment of depression for patients, rather than the cost assumed by third-party payers. The authors suggest that the reason for the cost savings for patients treated by psychiatric specialists

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 1 publication
0
17
0
Order By: Relevance
“…Cetirizine was previously identified as cross-reacting with fluorescence polarization immunoassays (30). Quetiapine was previously identified as cross-reacting with some marketed TCA screening immunoassays (7-9). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cetirizine was previously identified as cross-reacting with fluorescence polarization immunoassays (30). Quetiapine was previously identified as cross-reacting with some marketed TCA screening immunoassays (7-9). …”
Section: Resultsmentioning
confidence: 99%
“…Examples of published reports of DOA/Tox assay cross-reactivity include fluoroquinolone antibiotic cross-reactivity with opiates assays (5, 6), quetiapine cross-reactivity with tricyclic antidepressant (TCA) assays (7-9), fentanyl cross-reactivity with LSD immunoassays (10, 11), sertraline and sertraline metabolite cross-reactivity with benzodiazepine assays (12, 13), and venlafaxine and O -desmethylvenlafaxine cross-reactivity with PCP assays (14). …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, another antipsychotic drug, olanzapine showed only minimal crossreactivity (0.06%-0.7%) and did not interfere with the immunoassay used for TCA. 38 Cerullo et al commented that 5 patients who initially tested negative for TCAs tested positive after being treated with topiramate or quetiapine. A quetiapine trough blood level was obtained at the same time when urine toxicology screen of TCA was performed, and the results paralleled positive urinary TCA screen (when patients showed serum quetiapine levels between 5.1 and 85 ng/mL, urine TCA was also positive).…”
Section: Issues Of Interferences With Immunoassays For Tricyclic Antimentioning
confidence: 99%
“…The structure of quetiapine is similar to that of TCAs (both contain a similar tricylcic framework), and there have been two prior case reports in the literature that noted false positives for TCAs in adult patients taking quetiapine (1,2). Three in vitro studies (13) found false positive TCA results in some immunoassays using concentrations as low as 160 ng/ml of quetiapine.…”
mentioning
confidence: 99%
“…Three in vitro studies (13) found false positive TCA results in some immunoassays using concentrations as low as 160 ng/ml of quetiapine. To our knowledge, there have been no prior reports of cannabis or topiramate causing false positives for TCAs.…”
mentioning
confidence: 99%